FISH AND SEAFOOD PRODUCTION IN THE WORLD AND IN UKRAINE - DUKHNYTSKYI, Bogdan; SYDORENKO, Victor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines main indicators of fish and seafood production in the world and in Ukraine. The growth of world production since 2000 is shown. The largest producing countries of these products are determined, as well as the existing product structure of the global supply, which mainly consists of freshwater fish, marine fish, molluscs and crustaceans. The dynamics of extraction aquatic bioresources in Ukraine since the beginning of independence was analyzed. The regional structure of extraction, by fishing areas and species at the current stage, is given. The functioning of the industry in Ukraine after the full-scale Russian invasion is characterized, including the most significant changes and conditions of activity in 2022-2023. The key role of the state in the implementation of new principles and measures in the field of extraction of aquatic biological resources was noted. The main goals of the Strategy for the Development of Fisheries Industry in Ukraine until 2030 are listed. Prognostic assessments the indicators of the development of the world production fish and seafood are highlighted, including the growing role of the aquaculture sector. Despite the good prospects, the global fishing industry will face many uncertainties that can change numbers of the current forecasts. Particular attention is paid to the niche segment of production - organic aquaculture. Unlike the entire sector, here the product structure and the main producing countries are much clearer. All the problems that our fishing industry additionally faces during a full-scale war are listed. The most likely scenario relevant for Ukrainian fisheries and aquaculture for the coming years is formulated. Ukraine, most likely, will not be able to restore the previous volumes of extraction the aquatic biological resources, because this requires a real stabilization of the entire socio-economic situation in the country.
Keywords: fish; seafood; aquatic biological resources; aquaculture; production; extraction; strategy